2011
DOI: 10.1097/prs.0b013e31821e70e7
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Graft in Postmastectomy Pain Syndrome

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 20 publications
3
127
0
6
Order By: Relevance
“…Histologic examination showed patterns of new collagen deposition, local hypervascularity, dermal hyperplasia, and a high correspondence to healthy tissues [3]. The promising results obtained with burn scars led us to extend the use of lipostructure for several pathologic conditions requiring tissue remodeling [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Histologic examination showed patterns of new collagen deposition, local hypervascularity, dermal hyperplasia, and a high correspondence to healthy tissues [3]. The promising results obtained with burn scars led us to extend the use of lipostructure for several pathologic conditions requiring tissue remodeling [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][6][7][8][9][10][11][12][13][14][15][16] Nine of the 15 studies were classified as level IV (case series), two as level III (a retrospective cohort and a comparative clinical study), one as level II (prospective cohort study), and three were not classified (for dealing with animal studies or review articles). No level I studies were found, that is, those with the strongest evidence (controlled and randomized clinical trials).…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, the procedure presented a low rate of surgical complications and satisfactory evolution in the postoperative period. 15 A study by Moltó Garcia et al showed a rate of 3.35% for early complications from fat grafting, such as pain at the application site, seroma and Relief of cicatricial neuropathic pain due to improved quality of infection of the surgical wound. In relation to late-onset complications, this study indicated the presence of cysts at the fat grafting site (16.2% of cases) and calcifications (10.8% of cases).…”
Section: Discussionmentioning
confidence: 99%
“…Exploring all surgical options for the management of chronic pain relating to breast cancer is outside the scope of this review article; however, it is worth noting that Caviggioli et al have had success with autologous fat grafting in painful mastectomy scars [45]. A more recent study by Maione et al found similar improvement in pain scores with autologous fat grafting for women suffering from chronic pain after breast conservative surgery and radiotherapy, an increasingly popular method of surgical treatment for breast cancer [46].…”
Section: Advances In Interventional Procedures For Breast Cancer Relamentioning
confidence: 99%